2013
DOI: 10.6061/clinics/2013(01)oa16
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen decreases the myofibroblast count in the healing bile duct tissue of pigs

Abstract: OBJECTIVE:The aim of this study was to evaluate the effect of oral tamoxifen treatment on the number of myofibroblasts present during the healing process after experimental bile duct injury.METHODS:The sample consisted of 16 pigs that were divided into two groups (the control and study groups). Incisions and suturing of the bile ducts were performed in the two groups. Tamoxifen (20 mg/day) was administered only to the study group. The animals were sacrificed after 30 days. Quantification of myofibroblasts in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Tmx reduced the expression of α‐SMA in the healing tissue, suggesting a decrease in myofibroblast number (Siqueira et al . ). In a previous study in a rat model, it was reported that the antifibrotic effects of tmx are associated with reduced TGF‐β1 levels, which in turn is related to the reduction in postoperative adhesion in a dose‐ and time‐dependent manner (Karaca et al .…”
Section: Discussionmentioning
confidence: 97%
“…Tmx reduced the expression of α‐SMA in the healing tissue, suggesting a decrease in myofibroblast number (Siqueira et al . ). In a previous study in a rat model, it was reported that the antifibrotic effects of tmx are associated with reduced TGF‐β1 levels, which in turn is related to the reduction in postoperative adhesion in a dose‐ and time‐dependent manner (Karaca et al .…”
Section: Discussionmentioning
confidence: 97%
“…Through Masson staining, we found a large number of collagen fibers and smooth muscle fibers in the anastomotic stoma 1 month after the operation, and the fibers were disorderly and broken. The characteristics of scar formation in CJS are as follows (39)(40)(41): inflammatory cell infiltration and fibroblast activation appeared in the early stage of anastomotic stoma healing; with time, infiltration of inflammatory cells in the anastomotic stoma was gradually aggravated, fibroblasts and myofibroblasts proliferated, and collagen fibers and smooth muscle fibers increased significantly, and eventually led to the proliferation of granulation tissue and scar formation. If an early intervention can reduce the anastomosis's inflammatory reaction and the activation of fibroblasts, it could prevent CJS scars' formation.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that the transplanted bile duct patch did not survive but went through a process of destruction and regeneration. It is known that epithelial cells and periductal myofibroblasts are closely linked because damage to the former leads to activation and proliferation of the latter ( 23 , 24 ). Ki67 + cuboidal columnar epithelial cells were found within the columnar biliary epithelial and peribiliary glands.…”
Section: Discussionmentioning
confidence: 99%